cocassi function algebra 2

Algebra Level 4

x , y , z x, y, z are non-zero real numbers such that:

x+y=4xy
y+z=6yz
z+x=8zx

If x + y + z = a b x+y+z = \frac{a}{b} where a , b a, b are positive coprime integers, what is a + b a + b ?


The answer is 38.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Divyansh Singhal
Aug 26, 2014

Let x+y=4xy ..........(1) y+z=6yz ...........(2) z+x=8zx .............(3) Divide (1) by xy, Divide (2) by yz, Divide (3) by zx. Then you will get three equations

1.(1/x)+(1/y)=4

2.(1/y)+(1/z)=6

3.(1/z)+(1/y)=8

Three equation three variable and you will get x=1/3,y=1,z=1/5 x+y+z=23/15

Hence the answer is 23+15=38

I also did the exact same way!

Kartik Sharma - 6 years, 9 months ago

same here!!@@!!

Rudresh Tomar - 6 years, 8 months ago

quite beautiful and elegant solution!!!!!!!!!!!!!!!

Rayyan Shahid - 6 years, 7 months ago

Done the same way :)

Aman Sharma - 6 years, 6 months ago

@Divyansh Singhal and @Jai gupta The answer could also be x = y = z = 0 x=y=z=0

Otherwise, elegant solution.

Mehul Arora - 5 years, 9 months ago
James Wilson
Jan 8, 2021

I solved for y y in terms of x x in the first equation: y = x 4 x 1 . y=\frac{x}{4x-1}. Then I solved for z z in terms of y y in the second equation: z = y 6 y 1 . z=\frac{y}{6y-1}. Substituting the first equation into the second gives the complex fraction: z = x 4 x 1 6 x 4 x 1 1 . z=\frac{\frac{x}{4x-1}}{\frac{6x}{4x-1}-1}. After simplifying, I got z = x 2 x + 1 . z=\frac{x}{2x+1}. Next, I substituted x 2 x + 1 \frac{x}{2x+1} in for z z in the third equation: x 2 x + 1 + x = 8 x 2 x + 1 x \frac{x}{2x+1}+x=8\frac{x}{2x+1}x x + 2 x 2 + x = 8 x 2 \Rightarrow x+2x^2+x=8x^2 2 x = 6 x 2 \Rightarrow 2x = 6x^2 x = 1 3 . \Rightarrow x=\frac{1}{3}. Finally, substituting x = 1 3 x=\frac{1}{3} in y = x 4 x 1 y=\frac{x}{4x-1} and z = x 2 x + 1 z=\frac{x}{2x+1} , I get the final answer

( x , y , z ) = ( 1 3 , 1 , 1 5 ) (x,y,z)=(\frac{1}{3},1,\frac{1}{5}) .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...